Upaya Peningkatan Kesejahteraan dan Profesionalisme Tenaga Pendidik di SDN JERUK 1/ 469 SURABAYA - Wulandari, Rahma Ayu; Aj-Jaudah, Salsabila; Windasari, Windasari; Hanivia Cindy, Agustin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
Endeavors to progress the welfare and polished skill of teachers are vital angles within the advancement of a country's instruction. Teachers play a vital role in forming the quality of instruction as well as molding the character and states of mind of understudies. Be that as it may, they are frequently confronted with different challenges, such as tall workloads and a need for assets. The drive to improve the quality of education becomes progressively critical within the time of globalization, where quality instruction gets to be the key to worldwide competitiveness. Amid changing discernments of the instructing calling, there's a need for participation between the government, instructive education, and the community to plan and execute programs that bolster the welfare and polished skills of teachers. This theory outlines the importance of collaborative endeavors in creating a quality instructional environment that's prepared to confront future challenges.